PBL Model Experiment with Character Value Approach to Improve Cognitive, Affective, and Psychomotor Competencies in Physics Learning - Basri, Syamsuriana; Ibrahim, Misykat Malik; Yuspiani, Yuspiani; Shabir U, Muhammad (PT. Riset Press International, 2025)
This study aims to examine the effectiveness of Problem-Based Learning (PBL) model integrated with character values on improving students' cognitive, affective, and psychomotor competencies in physics learning. The research was conducted using One Group Pretest-Posttest experimental design on class X students at SMAN 1 Jeneponto, South Sulawesi. Data were collected through cognitive tests, psychomotor observation sheets, and affective questionnaires. The results of the analysis showed that the application of PBL-NK model significantly improved all three aspects of student competence. The highest average score was achieved in the psychomotor aspect (86.5), followed by the cognitive (84.6) and affective (80.5) aspects. This improvement was proven through paired t-test with significant results on all variables (p < 0.05). These findings indicate that PBL-NK not only improves the understanding of physics concepts, but also supports the formation of student character in accordance with the Pancasila Student Profile. This model proves to be relevant in answering the challenges of 21st century education through the integration of competency-based learning and character values. It is recommended that teachers receive special training to apply this model, and the development of PBL-NK-based teaching materials is carried out to support the implementation of Merdeka Curriculum in various subjects.